Optimal Design of the Fuzzy Navigation System for a Mobile Robot Using Evolutionary Algorithms. (21st February 2013) - Meléndez, Abraham; Castillo, Oscar; Valdez, Fevrier; Soria, Jose; Garcia, Mario
This paper describes the optimization of an integration block within the proposed navigation control system for a mobile robot. The control blocks that the integrator will combine are two Fuzzy Inference Systems (FIS) in charge of tracking and reaction control, respectively. The integrator block is called a Weighted Fuzzy Inference System (WFIS) and assigns weights to the responses of each behaviour block, to combine them into a single response.